Novel Semiconductor Cu(C3H3N3S3)3/ZnTiO3/TiO2 for the Photoinactivation of E. coli and S. aureus under Solar Light - Ximena Jaramillo-Fierro; María Fernanda Cuenca (Nanomaterials, 2022)
The use of semiconductors for bacterial photoinactivation is a promising approach that has attracted great interest in wastewater remediation. The photoinactivator Cu-TTC/ZTO/TO was synthesized by the solvothermal method from the coordination complex Cu(C3H3N3S3)3 (Cu-TTC) and the hybrid semiconductor ZnTiO3/TiO2 (ZTO/TO). In this study, the effect of photocatalyst composition/concentration as well as radiation intensity on the photoinactivation of the gram-negative bacteria Escherichia coli and the gram-positive bacteria Staphylococcus aureus in aqueous solutions was investigated. The results revealed that 25 mg/mL of photoinactivator, in a Cu-TTC:ZTO/TO molar ratio of 1:2 (w/w%) presents a higher rate of bacterial photoinactivation under simulated solar light (λ = 300–800 nm) in comparison to the individual components. The evidence of this study suggests that the presence of the Cu(C3H3N3S3)3 coordination complex in the ZnTiO3/TiO2 hybrid semiconductor would contribute to the generation of reactive oxygen species (ROS) that are essential to initiate the bacterial photoinactivation process. Finally, the results obtained allow us to predict that the Cu-TTC/ZTO/TO photocatalyst could be used for effective bacterial inactivation of E. coli and S. aureus in aqueous systems under simulated solar light.